Contemporary Islamic Renewal in Indonesia - Azra, Azyumardi (Kasarinlan: Philippine Journal of Third World Studies, 2008)
During the early years of Suharto’s presidency, tension and conflict between Muslim groups and the government was widely evident. This discord was a result of government policies which the Muslims felt would uproot the influence of Islam from Indonesian politics. Towards the end of the 1980s, however, Islam began to show some convincing signs of revival. The turning point of Islamic reinvigoration was the acceptance of Pancasila by Muslim mass organizations as the foundation of their socio-political activities, thus ending the mutual suspicion between Muslims and the government. A more recent indication of Islamic resurgence is the increasing number of Indonesian haj pilgrims to Mecca and the formation of important Islamic organization, the All-Indonesian Muslim Intellectual Association, which serves as the sounding board for the Muslims to influence public policy. To conclude, the revival of Islam came at a time when Indonesia was enjoying economic growth. The crucial question, therefore, is how to maintain the momentum for economic growth so as to avoid possible negative effects of an economic regression on the revival of Islamic life. Moreover, Muslim activists working for a genuine revival of Islam should also deal with the problem of how to eliminate, or at least reduce, un-Islamic practices such as corruption and poor discipline among Indonesian Muslims.